Technological and environmental performance of temperature-reduced mastic asphalt mixtures. Issue 1 (2nd January 2017) - Hofko, B.; Dimitrov, M.; Schwab, O.; Weiss, F.; Rechberger, H.; Grothe, H.
Abstract : Temperature reduction of mastic asphalt (MA) mixtures can decrease costs and energy demand, as well as health-relevant emissions of particulate matter throughout the life cycle. A state-of-the-art method for temperature reduction is wax modification of the bituminous binder to reduce its viscosity. In this paper, the results of an extensive study. On mechanical performance, particulate matter emission and life-cycle analysis of temperature-reduced MA are presented. Therefore, a reference MA is compared to three temperature-reduced MAs: a state-of-the-art reduction by modification with amide wax (AW) and an alternative method of substituting crushed aggregates by rounded ones. For both methods, a temperature reduction of 30°C can be realised. In addition, a combination of both methods, wax modification and use of rounded aggregates, is investigated. For this combination a reduction of 50°C is possible. The results show that the resistance to permanent deformation is not decreased by using rounded aggregates and that it can be doubled by employing AW regardless of the aggregate shape. Resistance to low-temperature cracking is not affected by any of the studied methods for temperature reduction. Emission analysis reveals that more than 80% of the emitted particulates are below 2.5 µm a.d. (aerodynamic diameter). From a life-cycle perspective, a main benefit of temperature-reduced MAs is the significant decrease in particulate emissions by up to 80% in case of 50°C temperature reduction. Also, up to 20% of production process energy can be saved when the mixing temperature is reduced by 50°C. Application of a wax additive reduces process energy costs, but increases the total life-cycle costs. Based on the considered scenarios, the application of additives is controversial and the substitution of crushed aggregates by rounded aggregates seems to be beneficial.